PREVENTIVE DETENTION - THE REAL DANGER WHICH SETTING THE DEFENDANT FREE IS FOR PUBLIC ORDER - Adrian, Constantinescu (Anales Universitatis Apulensis Series Jurisprudentia; No 15 (2012): ANNALES UNIVERSITATIS APULENSIS - SERIES JURIPRDENTIA, 2012)
As a rule, preventive detention is a severe measure brought upon those who are suspected of committing serious offenses. Therefore, taking in consideration the criminal procedure law and the protection of fundamental human rights, it is of utmost importance that this type of imprisonment is not allowed the possibility to be used in an excessive and abusive way, but in definite situations, with clearly defined limits and constant guarantee of human rights. Keywords : preventive detention, offense, criminal procedure law, protection of fundamental human rights , The European Court of Human Rights